Transformational School Leadership: Predictor of Collective Teacher Efficacy - Ramazan Cansoy (Sakarya University Journal of Education)
The purpose of this study was to examine the relationship between school principals' transformational leadership and collective teacher efficacy based on teachers' views. The sample were 293 teachers in elementary and middle schools located in the Uskudar district of Istanbul. The data were gathered through the Transformational Leadership Scale and the Collective Teacher Efficacy Scale. Correlation and Regression analyses were employed in the analysis of data. The results showed that the school principals' transformational leadership behaviors had a positive, moderate and significant relationship with collective teacher efficacy. Also, school principals' transformational leadership behaviors were positive and significant predictor of collective teacher efficacy. These findings show that transformational leadership behaviors of school principals are an important antecedent of teachers'common beliefs that they can enable student learning.